Associação da cárie dentária com indicadores antropométricos do estado nutricional em pré-escolares - Foschini, Ana Lígia Rozato [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP] (My University, 2012)
The purpose of this study was to examine the association of dental caries with anthropometric indicators of nutritional status in preschool children in the city of Araraquara, SP. The sample was selected in a probabilistic stratifi ed way. A dental examination was conducted to investigate oral status indicators – dmft index. The weight and height of the children were measured. The anthropometric indicators of weight/height (WHZ), height/age (HAZ), weight/age (WAZ) and body mass index (BMIZ) were calculated. For the study of the probability of occur dental caries according to the nutritional status applying the logistic regression analysis. In order to compare the dmft index of preschool children according to the nutritional status was conducted by the Kruskal-Wallis test. 602 preschool children participated of the study. The mean dmft of the preschoolers was 1.22±2.23. Of the preschoolers 8.64% were wasted, 1.66% underweight and 1.00% stunted. High prevalence of excess weight was observed (38.37%), with prevalence of obesity of 15.78%. There was no signifi cant statistical difference (p=0.7128) for the dmft index according to the nutritional status of the children and the probability of the preschoolers to have dental caries is independent of the nutritional status.

Realizou-se este estudo para verifi car a associação da cárie dentária com indicadores antropométricos do estado nutricional em pré-escolares de Araraquara, SP. A amostra foi selecionada de forma probabilística por estratos. Realizou-se exame clínico bucal para investigação do Índice ceod. Foram aferidas as medidas antropométricas de peso e altura. Foi realizado cálculo dos indicadores de peso para altura (ZPA), altura para idade (ZAI), peso para idade (ZPI) e Índice de Massa Corpórea (ZIMC). Realizou-se regressão logística simples para estudo da probabilidade de ocorrência de lesões de cárie segundo o estado nutricional. Para comparação de ceod dos pré-escolares segundo seu estado nutricional utilizou-se o teste de Kruskal-Wallis. Participaram do estudo 602 pré-escolares. O ceod médio dos pré-escolares foi de 1,22±2,23. Em relação aos indicadores antropométricos do estado nutricional observou-se 8,64% de défi cit de peso para altura, 1,66% de baixo peso e 1,00% de défi cit de altura para idade. Pelo IMC observou-se alta prevalência de excesso de peso (38,37%), com prevalência de obesidade de 15,78%. Observou-se diferença nãosignifi cativa (p=0,7128) no Índice ceod segundo o estado nutricional das crianças e a probabilidade do pré-escolar apresentar acometimento pela cárie dentária independe de seu estado nutricional.
Association of dental caries with anthropometric indicators of nutritional status in preschool children
Keywords: Nutritional status; Anthropometry; Dental caries; Child preschool; Estado nutricional; Antropometria; Cárie dentária; Pré-escolares